Institutional Ownership and Firms’ Thrust to Compete - Andreou, Panayiotis; Fiordelisi, Franco; Harris, Terry; Philip, Dennis (My University, 2021)
This paper provides evidence on the impact of transient (short-term) institutional investors on a firm's thrust to compete. A firm's thrust to compete, as an attribute of corporate culture, captures the relative importance of corporate values that push a firm to achieve shareholder value in the short term by emphasizing goal achievement, fast response to external information and enhanced competitiveness. We find that greater ownership by transient investors results in firms intensifying their future thrust to compete, suggesting that firms respond to these investors’ preferences and competitive pressures for achieving short-term value creation. In line with our expectations, this effect is not observed for firms with greater ownership by long-horizon institutional investors, who are incentivized to place their emphasis on long-term firm value over short-term gains. Our findings reveal that the composition of institutional ownership influences the organizational culture of firms in a non-homogeneous way. As such, we provide significant empirical insights for the ongoing debate on the implications arising from the behind-the-scenes engagement of institutional investors with management.
Keywords: Shareholder activism; Institutional investors; Blockholders